The effect of flavoured and non-flavoured tobacco on subjective experience, topography and toxicant exposure among waterpipe smokers. (25th November 2019) - Ben Taleb, Ziyad; Vargas, Mayra; Ebrahimi Kalan, Mohammad; Breland, Alison; Eissenberg, Thomas; Brown, David; Maziak, Wasim
Abstract : Introduction: Flavoured waterpipe (WP) tobacco is a major factor in the resurgence of WP smoking and a main attractant of WP use among youth. Yet, evidence of the effects of limiting flavour on WP smoker's experiences and exposures is limited. This study examined the impact of flavour manipulation on WP smokers' toxicant exposure and smoking experiences. Method: A total of 144 WP smokers attended two, 45 min ad libitum smoking sessions (flavoured vs non-flavoured tobacco) in a crossover design study. Participants completed a battery of questions assessing subjective smoking experiences. Exhaled carbon monoxide (eCO) and plasma nicotine concentrations were measured before and after the smoking sessions. Puff topography was recorded throughout the smoking sessions. Results: Compared with the non-flavoured WP tobacco, participants reported enhanced subjective smoking measures of satisfaction and enjoyment following smoking flavoured WP tobacco (ps <0.05). Although participants spent a longer time smoking flavoured tobacco, they took on average larger puffs while smoking the non-flavoured tobacco (ps <0.05). Greater levels of eCO were recorded following the non-flavoured tobacco session (p<0.05) compared with flavoured tobacco. No significant differences were observed in plasma nicotine concentrations between the two tobacco conditions. WP harm perception was higher among participants after smoking non-flavoured WP tobacco compared with their preferred flavour (p<0.05). Conclusion: Smoking the flavoured tobacco product was associated with enhanced subjective experiences compared with the non-flavoured, suggesting a potential role for flavour regulation in reducing WP use. Mixed results were observed for toxicants exposure in relation to smoking flavoured compared with non-flavoured products suggesting the need for a more comprehensive assessment of the effects of other tobacco constituents and additives on toxicant exposure in WP smokers.